PERAN KEPEMIMPINAN PAK DALAM MEMPERSIAPKAN PEMUDA KRISTEN BATULILOK MENUJU INDONESIA EMAS 2045 - Wilsye Claudia Malelak (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
The increasingly rapid development of technology and the lack of role models that can be role models for Christian youth who were born in an era where everything is ready instantly, this triggers a character that is difficult to form a habit and become a superior character not only intellectually but also spiritually who has an intimate relationship close to God so that the need for a study conducted using a case study approach in forming and preparing Christian youth Rote Ndao (Bokai- Batulilok village) to become a superior generation and ready to welcome the golden Indonesia in 2045 in terms of starting with relevant education that can build strong faith, understand Christian values, good character ethics, and ready to become a generation that brings agents of change towards the Golden Indonesia that is by bringing a bright light change to the world that is almost damaged thus, the current generations become Christian youth who bring back many souls and all for the sake of the glory of God himself and through leadership based on Christian religious education which also has a crucial role in achieving the success indicators of Christian youth who are more effective and able to contribute towards a superior Indonesia, namely the golden Indonesia 2045.